Abs. Issue 1 (November 2015) - Barlev, N.; Fedorova, O.; Lezina, L.; Piletsky, S.
Abstract : Discovery of new pharmacologically active small molecules is an important and rapidly expanding area of modern molecular pharmacology. Given a limited number of proteins that are druggable, it is important to identify as many chemical effectors as possible to define the best regimen of anti-cancer therapy in each particular case. An E3 ubiquitin ligase, Mdm2, which mediates ubiquitin-dependent degradation of the critical tumor suppressor p53, is a promising target for small molecule inhibitors. Using a hybrid approach which combines the rational design of small molecules selected from the virtual library and the high-content screening using cancer cell lines we discovered several new inhibitors of the p53-Mdm2 interaction. These compounds were able to activate and stabilize the p53 protein causing massive apoptosis preferably in p53-positive cells at rates higher than the well-known inhibitor of Mdm2, Nutlin-3. The molecular mechanisms of their action will be discussed. As another example of rational design of potential anti-cancer drugs, we will talk about artificial nano-Matrix-Imprinted -Polymers (MIPs) that recognize the structure of peptides and other biological molecules and thus dubbed as "plastic antibodies". We have generated such nanoparticles against the surface region of the oncogenic receptor, EGFR, which is overexpressed in many forms of solid tumors. Selection of the linear epitope for creating "plastic antibodies" against the receptor was performed by analysis of a three-dimensional structure of the protein. The obtained "plastic antibodies" were specific against the epitope of EGFR. These plastic antibodies when loaded with a genotoxic drug, doxorubicin, were able to specifically induce cell death of breast cancer cell lines that overexpress the EGFR receptor. Experiments in vivo using xenografts of breast cancer cell lines pre-incubated with these plastic antibodies in nude mice showed that they have a pronounced therapeutic effect. Furthermore, since the commercial drug, Cetuximab, recognizes an epitope of EGFR, different from the one recognized by our plastic antibodies, it is likely that the latter may increase the efficacy of the commercial monoclonal antibody. Collectively, we demonstrate that the rationally designed small molecules can be potent and specific drugs for anti-cancer therapy.